Efficient Separation of Propylene from Propane in an Ultramicroporous Cyanide‐Based Compound with Open Metal Sites. Issue 5 (17th November 2021) - Xie, Yi; Shi, Yanshu; Cui, Hui; Lin, Rui-Biao; Chen, Banglin
Abstract : Exploring porous materials for selective adsorptive separation of propylene from propane to replace the energy‐intensive cryogenic distillation technologies remains a great challenge due to the similarity of these two gases in physiochemical properties. Herein, an ultramicroporous material, nickel nitroprusside (Ni‐NP ), with open metal sites (OMS) for the highly efficient separation of propylene from propane under ambient conditions is reported. This material exhibits high C3 H6 /C3 H8 selectivity of 10.5 and uptake ratio of 1.68, with a remarkable C3 H6 uptake capacity of 79.9 cm 3 g −1 . Dispersion‐corrected density functional theory (DFT‐D) calculations reveal that the selective adsorption of C3 H6 is attributed to strong host–guest interactions on the OMSs as well as multiple weak hydrogen bonding within the compact pore space. The C3 H6 /C3 H8 separation performance is validated by breakthrough experiments, showing a high productivity of 2.30 mol kg −1 . This material can be facilely obtained by simple precipitation reaction under ambient conditions, which highlights its scale‐up potential for C3 H6 /C3 H8 separation. Abstract : Highly selective separation of propylene from propane is realized in an ultramicroporous material nickel nitroprusside (Ni‐NP ), featuring compact pore space with a density of open metal sites, which enables specific molecular recognition of propylene and high adsorption uptake under ambient conditions.